2018
DOI: 10.1002/cncr.31738
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world testing and treatment patterns in chronic lymphocytic leukemia: A SEER patterns of care analysis

Abstract: Background: Laboratory testing and treatments have changed dramatically in chronic lymphocytic leukemia (CLL) within the last decade. We evaluated changes in patterns of real-world testing and treatment over time by comparing two population-based cohorts. Methods: The National Cancer Institute (NCI) sponsored Patterns of Care study was conducted among CLL patients sampled from 14 Surveillance, Epidemiology, and End Results (SEER) program registries. Demographics, testing, and treatment data were abstracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 26 publications
6
22
3
Order By: Relevance
“…The finding that nearly two‐thirds of patients did not receive a cancer‐directed therapy after CLL diagnosis suggests that observation (“watch‐and‐wait”) was the preferred initial approach during the study period. Our study identified BR, rituximab monotherapy, ibrutinib monotherapy, and FCR as the most common regimens during the study period, which is consistent with the 2017 NCCN Guidelines and other recently published reports . Recently, 2018 NCCN Guidelines suggest chemoimmunotherapy (FCR/ BR) or ibrutinib as preferred treatment choices among younger patients (<65 years) who are relatively less frail and able to tolerate purine analogues .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The finding that nearly two‐thirds of patients did not receive a cancer‐directed therapy after CLL diagnosis suggests that observation (“watch‐and‐wait”) was the preferred initial approach during the study period. Our study identified BR, rituximab monotherapy, ibrutinib monotherapy, and FCR as the most common regimens during the study period, which is consistent with the 2017 NCCN Guidelines and other recently published reports . Recently, 2018 NCCN Guidelines suggest chemoimmunotherapy (FCR/ BR) or ibrutinib as preferred treatment choices among younger patients (<65 years) who are relatively less frail and able to tolerate purine analogues .…”
Section: Discussionsupporting
confidence: 88%
“…Our study identified BR, rituximab monotherapy, ibrutinib monotherapy, and FCR as the most common regimens during the study period, which is consistent with the 2017 NCCN Guidelines and other recently published reports. 5,21,22 Recently, 2018 NCCN Guidelines suggest chemoimmunotherapy (FCR/ BR) or ibrutinib as preferred treatment choices among younger patients (<65 years) who are relatively less frail and able to tolerate purine analogues. 23 The most common choice among LOT-1 regimens was BR, while ibrutinib was the preferred LOT-2 regimen, a finding that confirms results of another study 21 ; however, the proportion of ibrutinib users observed in our study was half of what has been reported (21% vs 42%), potentially because in our analysis ibrutinib was approved only in the later part of the study period.…”
Section: Discussionmentioning
confidence: 99%
“…5 The date of the first claim for one of these treatments following the first CLL/SLL diagnosis is the index date. 6 End-stage renal disease was identified using ICD-9 CM code 585.6 and ICD-10 CM code N18.6. All-cause total health care costs were stratified by medical and pharmacy costs.…”
Section: Study Measuresmentioning
confidence: 99%
“…[1][2][3] For many patients, rituximab-based CIT, such as bendamustine plus rituximab (BR) or fludarabine cyclophosphamide plus rituximab (FCR), was, until recently, the standard of care 4,5 ; overall, these regimens are still commonly utilized in real-world clinical practice. 6 Despite this progress, BR and FCR have limited efficacy in subgroups of patients with 17p deletions (a region that contains the TP53 locus). 1,[7][8][9][10] In addition, long-term safety concerns, including a higher risk of secondary myelodysplastic syndrome, acute myeloid leukemia, and transformation to diffuse large B-cell lymphoma (ie, Richter's transformation), are other limitations associated with CIT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation